Shirky and Sanger, or the costs of crowdsourcing - Mathieu O'Neil (JCOM: Journal of Science Communication, 2010)
Online knowledge production sites do not rely on isolated experts but on collaborative processes, on the wisdom of the group or “crowd”. Some authors have argued that it is possible to combine traditional or credentialled expertise with collective production; others believe that traditional expertise's focus on correctness has been superseded by the affordances of digital networking, such as re-use and verifiability. This paper examines the costs of two kinds of “crowdsourced” encyclopedic projects: Citizendium, based on the work of credentialled and identified experts, faces a recruitment deficit; in contrast Wikipedia has proved wildly popular, but anti-credentialism and anonymity result in uncertainty, irresponsibility, the development of cliques and the growing importance of pseudo-legal competencies for conflict resolution. Finally the paper reflects on the wider social implications of focusing on what experts are rather than on what they are for.